2021
DOI: 10.31729/jnma.5734
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Type 2 Diabetes among Patients Visiting Nepal Police Hospital in Kathmandu: A Descriptive Cross-sectional Study

Abstract: Introduction: The growing prevalence of diabetes mellitus (DM) is a critical threat for global health,including in Nepal, especially in Kathmandu District, where diabetic patients are increasing in hospitals catastrophically. This study tends to assess the prevalence rate of type 2 diabetes among admitted patients visiting a hospital in Kathmandu. Methods: An electronic chart review was done to assess the prevalence of type 2 diabetes in NepalPolice hospital, Kathmandu, Nepal. Ethical approval was taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…7 A systematic review carried out in 2014 showed a pooled prevalence of DM as 8.4%, with the variation in prevalence ranging from 1.4% to 19.0% in Nepal. 8 Even though, there are several national estimates available on the prevalence of DM in Nepal, [9][10][11][12] those studies were limited to small sample size or geographic location that would not be representative of the whole population in Nepal. In addition, criteria used for defining the prevalence of DM varied across studies.…”
Section: Open Accessmentioning
confidence: 99%
“…7 A systematic review carried out in 2014 showed a pooled prevalence of DM as 8.4%, with the variation in prevalence ranging from 1.4% to 19.0% in Nepal. 8 Even though, there are several national estimates available on the prevalence of DM in Nepal, [9][10][11][12] those studies were limited to small sample size or geographic location that would not be representative of the whole population in Nepal. In addition, criteria used for defining the prevalence of DM varied across studies.…”
Section: Open Accessmentioning
confidence: 99%